A True Person of No Status: Notes on Zen and the Art of Existential Therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
Zen calls an accomplished practitioner a ‘true person of no status’. ‘No status’ indicates the uncertainty of being thrown in the midst of an impermanent world. A ‘true person’ is open and vulnerable to the teachings of life itself. Existential therapy emphasises intrinsic autonomy, lived experience and the desertion of the surrogate of status, but it has relied for too long on Heidegger’s idea of authenticity, a notion which reinstates idealist philosophy and monistic notions of ‘Truth’. Alternatives to the idea of authenticity are the notions of openness, vulnerability, and integrity (the latter understood as reluctance to give in to the compulsion of system-building) Both Zen and existential therapy are at variance with the manipulative, state-sponsored modes that constitutes mainstream psychotherapy today. They provide inspiration for credible and organized acts of defiance in response to the demands of the market and the philistine pragmatism that dominates our current Zeitgeist.
Keywords: the everyday; authenticity; uncertainty; integrity; openness; vulnerability.